2021
DOI: 10.3390/jcm10235544
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Different Lymphatic Drainage Patterns during Sentinel Lymph Node Biopsy for Skin Melanoma

Abstract: In the last two decades, studies of lymphoscintigraphy imaging in lymphatic mapping reported an extreme heterogeneity of skin lymphatic drainage of some skin area, in contrast with the previous scientific literature. The aim of this study was to investigate the presence of any correlations between the topographical location of cutaneous melanoma and the topographical location of sentinel lymph nodes. Data from 165 patients undergoing sentinel lymph node biopsy between January 2013 and May 2021 were analyzed, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…[11,26] It is under this assumption that our results regarding number of identified LNs must be interpreted, thus relativizing the seemingly reduced sensitivity of ICG based on the number of LNs identified transcutaneously in comparison to LS (79.4% sensitivity). However, as Cirocchi et al [27] described in their study, trunk malignant melanoma (especially lumbar, scapular, and subscapular) have a heterogenous drainage pattern, meaning that they can drain in multiple and/or bilateral nodal basins. In our study, ICG was able to identify in 4 patients with trunk malignant melanoma additional nodal basins.…”
Section: Discussionmentioning
confidence: 91%
“…[11,26] It is under this assumption that our results regarding number of identified LNs must be interpreted, thus relativizing the seemingly reduced sensitivity of ICG based on the number of LNs identified transcutaneously in comparison to LS (79.4% sensitivity). However, as Cirocchi et al [27] described in their study, trunk malignant melanoma (especially lumbar, scapular, and subscapular) have a heterogenous drainage pattern, meaning that they can drain in multiple and/or bilateral nodal basins. In our study, ICG was able to identify in 4 patients with trunk malignant melanoma additional nodal basins.…”
Section: Discussionmentioning
confidence: 91%
“…The data we obtained underline how cutaneous melanoma presents an extremely heterogenous lymphatic drainage at the level of the axillary cavity. A previous study by Cirocchi et al [ 28 ] had shown how the lymphatic drainage of cutaneous melanoma is extremely heterogenous: it is more various if compared to the topographic localization of the lymph nodes at the level of the axillary cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, its off‐label use has been broadened and rapidly expanding, where it has been described in intravascular organ perfusion, hepatic clearance, pulmonary imaging, ureter identification, and lymphatic imaging. Its use for mapping of sentinel lymph nodes has been described in adult malignancies including melanoma, 20,21 breast, 22–26 endometrial, 27,28 colorectal, 29–33 pulmonary, 34,35 and gastric cancer 36,37 . These studies have looked at application of ICG in the adult population, but similar studies are lacking in pediatric surgical oncology.…”
Section: Introductionmentioning
confidence: 99%